PEMANFAATAN LIMBAH DAUN KELAPA SAWIT YANG DIKOMPOSKAN DAN PENGARUHNYA TERHADAP PENINGKATAN PRODUKSI MENTIMUN YANG DIBERI PUPUK AN-ORGANIK - Maizar Maizar (DINAMIKA PERTANIAN, 2015)
This research aims to examine the effect of compost made from waste oil palm leaf on increasing production of cucumber, the use of the best compost on cucumber production and the reducing level of using orgnic fertilizer with compost substitution on vegetable. The experiment used the completely randomized design with two factors. The first factor was oil palm. Leaf compost with four treatments: 0, 5, 10, 15 t/ha. The second factor was an-organic fertilizer with four treatments: 0, 1/3, ½ and 1 times the recommended dose. The result showed that interactinally application of various dose of compost and anorganic fertilizer has effect on all parameters observations. The using palm leaf compost 10 t/ha increase cucumber production to 20 t/ha compared to control and reduce the use of inorganic fertilizers into ½ times the recommended dose.